Yahoo Web Search

  1. Sort by

  1. ...(θ/2)) = |cos(θ/2)| = cos(θ/2) ..... since cos(θ/2) > 0 for 0 ≤ θ ≤ π = LHS

    3 Answers · Science & Mathematics · 03/12/2017

  2. .../cosA 1 - sin²A = cos²A Starting with the LHS we have : ∴ LHS = [(secA + tanA) /(secA - tanA...

    4 Answers · Science & Mathematics · 20/11/2017

  3. LHS = (secA-cosA)/(cosA-sinA) = (1 - cos²A...

    2 Answers · Science & Mathematics · 18/11/2017

  4. LHS: csc θ - cot θ = 1/sin θ - cos θ/sin θ = (1 - cos θ)/sin θ Multiply...

    1 Answers · Science & Mathematics · 08/11/2017

  5. ... - cos2A = 2sin(B + A)sin(A - B) LHS = [2cos(A + B)cos(A - B)] /[2sin(B + A)sin...

    1 Answers · Science & Mathematics · 21/10/2017

  6. LHS= cos(4x)+cos(6x)-cos(2x)-1= cos(4x)+cos(6x)-2cos^2(x)= 2cos(5x)cos(x)-2cos^2(x)= 2cos(x)[cos(5x)-cos(x)]= 2cos(x)[-2sin(3x)sin(2x)]= -4cos(x)sin(3x)sin(2x)= RHS

    2 Answers · Science & Mathematics · 21/10/2017

  7. 5/6x=-2/18 multiply LHS by 3/3 15/18x = -2/18 multiply both sides by 18 15x = -2 divide both ...

    6 Answers · Science & Mathematics · 16/10/2017

  8. ... + sin B) = (sin B - sin A) / (cos A + cos B) LHS = (cosA - cosB)/(sinA + sinB) {multiply by conjugate of...

    4 Answers · Science & Mathematics · 14/10/2017

  9. ... then balance the charges by putting in electrons on the LHS. Zn = Zn^2+ + 2e^- Cr2O7^2- + 14H^+ + 6e^- = 2Cr...

    1 Answers · Science & Mathematics · 08/10/2017

  10. ...)cos(2A) and 2−2cos(4A) = 4sin²(2A) ∴ LHS = 4sin²(2A)(1−cos(2A)) = 4(4sin²Acos²A)(...

    1 Answers · Science & Mathematics · 03/10/2017

  1. Try asking your question on Yahoo Answers